(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2014)
Durban, a city situated on the South-Eastern end of Africa, cannot be stamped with any one particular identity. While the colonial city was planned, the Warwick Junction Precinct evolved around the needs and aspirations of people in time. This however, was never planned, nor ever meant to be as it was the sheer resilience of marginalised people that built this "parallel definition" which makes Durban so unique. In order to understand how this came about it is necessary to trace the historical evolution of Durban. Three major periods define its evolution: the British Union Period, the Boer Republic and the Post-apartheid period. While planning principles and legislation defined the development and character of the historically "white" CBD, resilience and adaptation over time defines the character of the Warwick Junction Precinct as a complex and unique place in Durban.